Epistemological Beliefs and Academic Performance in Physics of Grade 12 Filipino STEM Learners - Panergayo, Albert Andry Echor; Gregana, Clarissa Fajardo; Panoy, Julie Fe Dimaunahan; Chua, Elisa Nocheseda (FKIP Universitas Lampung, 2023)
Epistemological Beliefs and Academic Performance in Physics of Grade 12 Filipino Stem Learners. Objectives: This descriptive-correlational study investigated the existing relationship of epistemological beliefs to the academic performance in Physics of Filipino STEM learners. It further described the levels of academic performance and sophistication of epistemological beliefs about Physics of the Filipino STEM learners. Methods: This study involved a convenient sample of 407 Grade 12 Filipino STEM learners enrolled in A. Y. 2021-2022. This study used EBAPS to solicit the epistemological views of the students in Physic. Findings: Frequency, mean and standard deviation shown that majority of the students have a very satisfactory academic performance but their epistemological beliefs about Physics are generally poorly sophisticated. Pearson product-moment coefficient revealed that the four non-orthogonal dimensions of epistemological beliefs about Physics (structure of scientific knowledge, nature of knowing and learning, evolving knowledge, source of ability to learn) established significant association to students’ academic performance except real-life applicability. Multiple regression analysis revealed that among five dimensions of epistemological beliefs structure of scientific knowledge and nature of knowing are found to be significant determinants of the students’ academic performance in Physics. Conclusions: It is recommended for the physics teachers to craft an instructional intervention to enhance the students’ epistemological beliefs in physics, which in turns affect the performance of the students in the class. Keywords: academic performance, epistemological beliefs, multiple regression.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202302